Improved softened membrane model for prestressed composite box girders with corrugated steel webs under pure torsion. (February 2019) - Zhou, Cong; Li, Lifeng; Wang, Lianhua
Abstract: In this study, a theoretical model called the improved softened membrane model for torsion (ISMMT) is proposed for evaluating prestressed composite box girders with corrugated steel webs (PCBGCSWs) under pure torsion. First, considering the mechanical properties of PCBGCSWs, a series of equations are derived from equilibrium and compatibility conditions and constitutive relationships of the materials. In the equations, the criteria of shear flow equivalence and shear strain equivalence are adopted to determine the relationships between the concrete flanges and the corrugated steel webs (CSWs) before and after the yielding of the CSWs, respectively. Then, the solution algorithms, including a general algorithm for the entire torsional process and a simplified algorithm for the stage when both steel bars, the prestressing steel and the CSWs are in the elastic state, of the ISMMT are presented to solve all the equations. To validate the feasibility of the proposed theoretical model, the experimental results of a prismatic PCBGCSW under pure torsion available in the literature are selected for comparison. Additionally, a three-dimensional (3D) finite element (FE) model of the specimen is established using ABAQUS software. The results from the theoretical model, including the overall torque-twist curve, shear strain in the CSWs and strains in the prestressing steels and steel bars, are compared with those from the FE model and the experiment. The theoretical, numerical and experimental results are in good agreement, demonstrating that the proposed analytical model accurately predicts the torsional behaviour of the PCBGCSWs under pure torsion, including the torsional behaviour during the pre- and post-cracking stages. Highlights: A theoretical model (ISMMT) is proposed for evaluating PCBGCSWs under pure torsion The general and simplified solution algorithms of the ISMMT are proposed The feasibility of the ISMMT is validated by the numerical and experimental results The criteria for determining the relationships between the concrete flanges and the CSWs are proved to be reasonable